Sleep Duration and Cancer in the NIH-AARP Diet and Health Study Cohort - Gu, Fangyi (PLoS One, 2016)
BACKGROUND: Very few studies have examined sleep duration in relation to cancer incidence with the exception of breast cancer. METHODS: We assessed the associations between sleep duration and incidences of total and 18 site-specific cancers in the NIH-AARP Health and Diet Study cohort, with 173,327 men and 123,858 women aged 51–72 years at baseline. Self-reported sleep duration categories were assessed via questionnaire. We used multivariable Cox proportional hazards regression to estimate hazard ratios (HR) and 95% confidence intervals (CI), using 7–8 hours/night as the reference. RESULTS: We observed a significantly increased risk of stomach cancer among male short sleepers (multivariable HR(5-6 vs. 7–8 hours) = 1.29; 95%CI: 1.05, 1.59; P(trend) = 0.03). We also observed suggestive associations in either short or long sleepers, which did not reach overall significance (P(trend) >0.05), including increased risks in male short sleepers for cancers of head and neck (HR(<5vs.7-8 hours) = 1.39; 95%CI:1.00–1.95), bladder (HR(5-6vs.7-8 hours) = 1.10; 95%CI:1.00–1.20), thyroid (HR(<5 vs. 7–8 hours) = 2.30; 95%CI:1.06, 5.02), Non-Hodgkin Lymphoma (NHL) (HR(5-6vs.7-8 hours) = 1.17; 95%CI:1.02–1.33), and myeloma (HR(<5vs.7-8 hours) = 2.06; 95%CI:1.20–3.51). In women, the suggestive associations include a decreased total cancer risk (HR(<5vs.7-8 hours) = 0.9; 95%CI:0.83–0.99) and breast cancer risk (HR(<5vs.7-8 hours) = 0.84; 95%CI:0.71–0.98) among short sleepers. A decreased ovarian cancer risk (HR(≥ 9 vs. 7–8 hours) = 0.50; 95%CI:0.26–0.97) and an increased NHL risk (HR(≥ 9 vs. 7–8 hours) = 1.45; 95%CI:1.00–2.11) were observed among long sleepers. CONCLUSION: In an older population, we observed an increased stomach cancer risk in male short sleepers and suggestive associations with short or long sleep duration for many cancer risks in both genders.